Teknik Reduksi Energi pada Perancangan Data Logger Parameter Matahari - M. Ikhsan; Yuwaldi Away (Jurnal Rekayasa Elektrika, 2014)
The research discusses about the energy saving techniques in the design of data logger devices based on AVR microcontroller for monitoring parameters of the air temperature and sunlight intensity in the visible light spectrum. These energy reduction techniques include hardware aspects such as the use of the minimum system, peripherals power supply control and software such as sleep-mode. When the intensity of sun light increases, the interrupt pin will activate the system, otherwise the system is in a state of sleep-mode. The electrical energy consumption of the data logger is continuously observed and recorded on an external memory (SD card) in real-time as so the 24 hours energy consumption can be known and the long-term-used energy can be predicted. Based on the results of measurements and calculations it is known that it takes energy of 8.23 Wh to turn the data logger for 24hours. With this reduction technique, the data logger energy consumption can be reduced by 68.5%.Keywords: data logger, energy saving, sun, sleep mode, interrupt